Nipah and its Current Situation in Indonesia - Sendow, Indrawati; Adjid, R M Abdul (Indonesian Bulletin of Animal and Veterinary Sciences, 2005)
Recently, the incidence of zoonotic disease in the world increases, due to technology development, human activities and ecosystem changes . One of these diseases is an outbreak of Nipah in the neighbouring country, Malaysia, which caused 105 people died and more than one million pig were culled . Malaysia is the adjacent country to Indonesia, hence, it is possible that Nipah will be transferred to Indonesia through imported pigs and their products, and the migration of wild animal such as fruit bat. Because of Nipah is one of emerging diseases and hazardous to human, it needs a serious attention . Preliminary results on Nipah serology at the Research Institute for Veterinary Science . Bogor .. indicated that pigs in Riau. North Sumatera . North Sulawesi and West Jawa areas were negative to Nipah virus infection . However, the reservoir host, fruit bats from North Sumatera, West Java and East Java areas had been proven to have antibodies against Nipah virus using both ELISA and serum neutralization tests . With this condition, human and animal health departments should anticipate a possible occurrence of Nipah viral infection in Indonesia . This paper reviewes many aspects of Nipah included aetiology, epidemiology, the situation in Indonesia, prevention and controlling recommendation, that can be used as an input in order to improve veterinary public health in Indonesia. Key words: Nipah, aetiology, epidemiology, controlling, Indonesia